Combined Effect of Active Packaging of Polyethylene Filled with a Nano-Carrier of Salicylate and Modified Atmosphere to Improve the Shelf Life of Fresh Blueberries - Valeria Bugatti; Maria Cefola; Nicola Montemurro; Michela Palumbo; Laura Quintieri; Bernardo Pace; Giuliana Gorrasi (Nanomaterials, 2020)
Blueberries are popular among consumers for their high nutritional value but are highly perishable due to the microbial decay. The use of active packaging that is able to interact with the food through releasing or absorbing substances can be a valid approach to preserve the quality and increase the fruit’s shelf-life. In this paper, an active packaging based on polyethylene (PE) filled with a nano-carrier of salicylate was prepared and characterized. Fresh blueberries were packaged in passive modified atmosphere packaging (pMA) for 13 days at 8 °C. The combination of the active filler in bulk and pMA showed a significant inhibition of mold development and a reduction of the respiration rate of fruits. Moreover, the release of salicylate on blueberries did not alter the fruits’ sensory traits and preserved the firmness and the nutritional quality. Finally, the combination of active packaging and pMA resulted a valid solution to extend blueberries’ shelf-life up to 13 days.